A study on post pandemic psychological changes towards managing work life and reinventing work life balance at Wunderman Thompson - Afsin, Syed Mashaiat (Brac University, 2022)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.